MAXIMIZING STUDENTS’ LEARNING EXPERIENCE THROUGH DIFFERENTIATED INSTRUCTIONS IN AN ICT-INTEGRATED ENVIRONMENT - Salleh, Nurhidayah Binte Mohd (PEOPLE: International Journal of Social Sciences, 2016)
Singapore’s education landscape is weaved in a collage of diverse learning profiles due to her multi-faceted society. A multitude of teaching strategies is thus imperative to cater to a classroom of diverse learners who differ not only culturally and linguistically but also in their cognitive abilities, background knowledge and learning preferences. It thus becomes mandatory, to explore different strategies to ensure and maintain high level of engagement and motivation throughout the lesson. Tomlinson (2004c) points out that the teacher is the professional in the classroom, using appropriate techniques, assisting each learner to reach his or her potential within the learning context. Thus, in an effort to maximize all students’ learning experience, there are significant efforts made by teachers to implement differentiated instructions. According to Tomlinson and Strickland (2005), teachers usually differentiate instruction by adjusting one or more of the following: the content; the process; or the product. This paper explicates how this possibility has been applied in an ICT-based teaching and learning programme known as 10 IS Aksara for Malay Language. This programme, which is done in collaboration with schools, is initiated by the Educational Technology Division (ETD) of the Ministry of Education (MOE), Singapore. It adopts a learner-centered approach which is well-balanced between teacher facilitated activities and web-based individual assignments. The availability of an online personalized learning space, incorporating the thoughtful blend of face-to-face and 1:1 online learning allows for multitude of possibilities for the teacher to design differentiated lessons to cater to the different abilities. From the point of content selection to the final individual online assessment, differentiated Instruction is carefully weaved in seamlessly throughout the lesson.Through such lessons, it was evident that there was a significant impact on the students final output. Students with lower learning ability were able to relate better in a non-threatening environment when the assignments were pitched at their level and thus became more confident learners. Assignments given to higher learning ability students, on the other hand, were more challenging. These provided them the opportunity to further explore and expand their learning experience.